Medialized, Muscle-Splitting Approach for Posterior Lumbar Interbody Fusion: Technique and Multicenter Perioperative Results. (April 2016) - Khanna, Nitin; Deol, Gurvinder; Poulter, Gregory; Ahuja, Arvind
Abstract : Study Design: Retrospective, multicenter study of perioperative results Objective: The purpose of this study was to describe the surgical technique for medialized posterior lumbar fusion as well as present preliminary complication and treatment results from a multicenter retrospective study. Summary of Background Data: Posterior exposures remain the most commonly performed approaches for spinal fusion. Conventional open posterior exposures, however, have relatively high exposure-related morbidity and postoperative infection rates. Less invasive exposures for transforaminal and anterior (lateral) interbody fusion have been widely used over the past decade, but the need for bilateral posterior exposure has challenged the development of less invasive exposures for direct posterior approaches for lumbar fusion. Methods: Consecutive patients treated with minimally invasive spine (MIS) posterior lumbar interbody fusion with medialized cortical bone trajectory pedicle screw and rod fixation were identified from four sites in the United States. Of the 138 patients identified, 61% of patients were treated for degenerative spondylolisthesis at 167 levels, most commonly at L4–5 (62%). Perioperative treatment, complication, and reoperation data were collected to describe early feasibility of the approach. Results: Mean total operative time was 135 minutes with an average of 236 mL of blood loss. Mean total postoperative length of hospital stay was 2.6 days, with 25% of patients discharged on the same day or within 23 hours of surgery. Total perioperative complication rate in 138 patients was 10.1% (14/138) with three related reoperations. Intraoperative complications included five (3.6%) instances of incidental durotomy, without any progression to persistent cerebrospinal fluid leaks. Nine (6.5%) postoperative complications occurred, including one L5 vertebral body fracture, two pulmonary embolisms, one deep vein thrombosis, one urinary tract infection one instance of urinary retention, two superficial surgical site infections, and one patient with persistent pain at 6 months postoperative. Three (2.2%) reoperations were performed, one for revision of the L5 vertebral body fracture, and two for wound debridement. No instances of postoperative radiculitis or neurological injury were observed. Conclusion: Medialized, muscle-sparing posterior exposures with specialized instrumentation can be performed in patients with degenerative lumbar pathology with low surgical morbidity and blood loss and a short length of postoperative hospital stay. Level of Evidence: 4